EFFECTS OF DIFFERENT RESISTIVE TRAINING PROTOCOLS ON STRENGTH (Fiep Bulletin - online, 2011)
Summary: In virtue of diverse inconclusive results in relation to the intensity and the type of beneficial exercises for the profit of muscular hypertrophy, the present work considered to compare the method prescribed of exercises for the ACMS (2002), with a fiche personalized mounted for the pupil through the theoretical and practical knowledge of the professional of physical education in the attainment of results. The work was carried out with a group of 30 pupils of an Academy of Muriaé-MG, divided in Control Group (CG) and Experimental Group (GE). The work with each integrant one lasted around 3 the 4 months of duration, and the collected data had been analyzed through Test t, using a level of significance of p
Keywords: Resistive training; Muscular Hypertrophy